A numerical assessment of the scale effects of a ship advancing through restricted waters. (1st June 2021) - Terziev, Momchil; Tezdogan, Tahsin; Incecik, Atilla
Abstract: Restricted waters present several challenges for ship builders and operators. The proximity of the seabed and river or canal banks cause viscous effects to be more pronounced than in unrestricted waters. These effects do not follow a linear scaling law, which is typically assumed in terms of sinkage and trim. Moreover, the resistance of the ship is increased in a complex fashion, which has largely eluded researchers. The present study will aim to elucidate scale effects in shallow water performance predictions. Particular attention is placed on the form factor, wave resistance, and frictional resistance. Scale effects are confirmed in the two former parameters. Justification for the obtained results is sought in terms of flow properties. Specifically, the flow velocity and boundary layer thickness are examined in detail. The selected case-study reflects recent experimental work on the KCS hull form in restricted waters. Highlights: Scale effects on ship performance are assessed via a RANS solver in restricted water. Reynolds number dependency is shown in the wave resistance coefficient and form factor. The obtained data is compared to recently published estimates. Good agreement is found between the present research and other research works.